2011
DOI: 10.1590/s0034-71672011000600008
|View full text |Cite
|
Sign up to set email alerts
|

Barreiras ao tratamento da hipertensão arterial

Abstract: The objective was to describe the barriers faced by people with hypertension for non compliance to treatment and control the levels of blood pressure. This is a transversal and descriptive study which was carried out in 6 basic health units in Fortaleza-Ceará, Brazil. The population consisted of 246 people enrolled in the program to Control Hypertension for at least a year. Data were collected using a structured interview and electronic chart. Of them, 69 showed normal blood pressure levels. The main barriers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0
41

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 8 publications
2
10
0
41
Order By: Relevance
“…4 Os profissionais de enfermagem que desejarem implantar intervenções visando adequação da dieta dos portadores de hipertensão, precisam antes compreender que impor hábitos por si só, não é suficiente para mudança de comportamentos em saúde. Um estudo realizado em Campinas, São Paulo, em 2012, com 49 portadores de hipertensão mostrou uma dificuldade dos enfermeiros para desenvolver planos de ação para o consumo de sal nos alimentos.…”
Section: Evidências Encontradas Na Literaturaunclassified
See 1 more Smart Citation
“…4 Os profissionais de enfermagem que desejarem implantar intervenções visando adequação da dieta dos portadores de hipertensão, precisam antes compreender que impor hábitos por si só, não é suficiente para mudança de comportamentos em saúde. Um estudo realizado em Campinas, São Paulo, em 2012, com 49 portadores de hipertensão mostrou uma dificuldade dos enfermeiros para desenvolver planos de ação para o consumo de sal nos alimentos.…”
Section: Evidências Encontradas Na Literaturaunclassified
“…3 De modo geral, o tratamento de qualquer doença crônica não transmissível representa profundo desafio para os pacientes, família e profissionais de saúde, principalmente enfermeiros, sobretudo porque o desaparecimento de sintomas, logo no seu início, induz a pessoa adoecida a acreditar que a doença foi curada. 4 A adesão ao tratamento da HAS não se restringe apenas à esfera física e à terapia farmacológica, também estão implícitas a experiência de vida e a subjetividade no processo de adoecer e de cuidar de si. Assim, as principais dificuldades de adesão ao tratamento se relacionam à desconfiança quanto à composição do fár-maco, à desvalorização da alopatia, à toxicidade causada pela medicação, às dificuldades de acesso e vínculo frágil com o sistema de saúde, às condições econômicas, aos efeitos indesejáveis das medicações hipotensoras que interferem no cotidiano, o esquecimento para tomar a medicação, etilismo, analfabetismo e a descrença quanto à cronicidade da HAS.…”
Section: Introductionunclassified
“…Desta maneira, ele poderá colaborar na minimização das barreiras ao tratamento anti-hipertensivo, por meio de orientações, incentivo, acolhimento, escuta qualificada, uso dos recursos disponíveis no serviço para complementar a assistência, valorização de suas dificuldades, medos e objeções ao tratamento (GUEDES et al, 2011).…”
Section: Introductionunclassified
“…3112 motivation to comply with the treatment plan, the empowerment of individuals against their treatment and technical preparation for disease management are some of the elements identified as roles of health professionals to achieve adherence to the diabetes regimen and, concomitantly, as limiting the role of these professionals in that they do not realize. 2,7,9 In this direction, there is a perceived paucity of studies which approaches are focused on limiting found / pointed out by health professionals and the coping strategies implemented in relation to diabetes with a view to treatment adherence. Thus put, this study seeks through an integrative review of literature about the range of health professionals in the process of adherence to treatment of people with diabetes and related coping strategies aimed at your face.…”
mentioning
confidence: 99%
“…2,7 , for professionals, organizational elements limiting membership becomes anchored in the service routines and in the work process.…”
mentioning
confidence: 99%